Cognitive Biases Affecting the Maintenance of COVID-19 Pandemic: COVID-19 Cognitive biases - Mohamed, Kawthar; Yazdanpanah, Niloufar; Saghazadeh, Amene; Rezaei, Nima (Acta Biomedica Atenei Parmensis, 2021)
All the countries and regions have already been infected with novel coronavirus disease (COVID-19). This super small guest has paralyzed the economy of the entire world, from the extreme fall of the oil prices to the bankruptcy of the great companies or even the small retail shops. The people’s lifestyle is undergoing significant changes, by which it is leaving a negative impact on their psychological and physical health. The atmosphere is filled with dual accusations from each one of the governments and their citizens. Recognizing cognitive biases that have potentially affected decision-making during the COVID-19 pandemic would help in considering some behavioral changes for curbing this global viral infection.